Radiation Utilization Efficiency, Nitrogen Uptake and Modeling Crop Growth and Yield of Rainfed Rice under Different Nitrogen Rates - Sucharita Mohapatra, Gouranga Kar, Ashwani Kumar and (Journal of the Indian Society of Soil Science, 2014)
Optimum utilization of photosynthetically active radiation (PAR) along with proper nitrogen (N) management for sustainable rice production is still a promising management recommendation for sustainable rainfed rice cultivation in eastern India. The objective of this investigation was to study radiation utilization efficiency (RUE), N uptake and modeling growth and productivity of wet/ rainy season rice (cv. Lalat and Gayatri) under 0, 50, 90, 120 and 150 kg ha-1 N application. Results showed that N rates significantly affected plant biomass, leaf area index (LAI), biological yield (straw and grain yield) and N uptake for both the varieties. The intercepted photosynthetically active radiation (IPAR) and spectral reflectance based vegetation indices (IR/R, NDVI) were also different between two varieties and among N rates. Higher rate of N increased the RUE significantly; averaged over years and varieties, mean values of RUE were 1.35, 1.70, 2.01, 2.15 and 2.17 g MJ-1 under 0, 50, 90, 120 and 150 kg N ha-1, respectively. Though crop growth, yield, N uptake and RUE were higher at 150 kg N ha-1 but the results were at par with 120 kg N ha-1. Agronomic N use efficiency (ANUE) was also low at 150 kg N ha-1. The DSSAT v 4.5 model was applied to simulate crop growth, yield and phenology of the crop under different N rates. Model performance was found to be poor at low N rates (0, 50 kg N ha-1), but the model performed fairly well at higher N rates (90 kg ha-1 and above).